Inguinal hernia: a view from the 21st century (a review) - V.V. Makarov; V.V. Nehoduiko; V.M. Feskov; O.H. Petiunin; M.Yu. Syzyi (Медицина неотложных состояний)
The proposed review is a look at the pathogenesis of inguinal hernia from the standpoint of molecular biology, as well as an attempt to understand the problems that are a consequence of explantation: issues of male fertility, chronic inflammation, carcinogenesis. It is proven that the pathogenesis of inguinal hernia is not reduced to a defect of the anterior abdominal wall. Moreover, the formation of this defect is preceded by a complex of modification of connective tissue components, which is based on the separation of the processes of extracellular matrix synthesis and matrix degradation with the predominance of the latter that disrupts the rotation of structures responsible for mechanical strength and elasticity. From this point of view, inguinal hernia is a multifactorial and heterogeneous disease.